Mother's Knowledge About Nutritional Needs About Weight Gain During Pregnancy at Manda Clinic - Rizky Andriani Bakara (Institute of Computer Science (IOCS), 2019)
Mother's Knowledge of Nutritional Needs Regarding Weight Gain During Pregnancy, it is necessary to know that for this reason, there is an activity to deliver material on contraceptives which is an effort to help with Nutritional Needs and Weight Loss During Pregnancy. Energy requirements for a normal pregnancy require an additional 80,000 calories over a period of approximately 280 days. This means that you need an extra 300 calories per day during pregnancy. The results of the activity still need to be developed so that pregnant women pay more attention to weight gain during pregnancy.